RESEARCH OF GUIDELINES FOR DESIGNING E-STUDY MATERIALS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
E-study use is increasing; its main content is information for self-education and it is delivered to the user through modern technologies that provide greater opportunities. In order to reach the user, information must be presented in a comprehensible and easy to remember way. The article focuses on the recommended ways of information presentation in e-studies, so that it would be possible to perceive and memorize information more efficiently, it also focuses on technologies that could help in building and analysing ways of presentation. There are analysed several technology products and presented various examples. The authors offer recommendation Guidelines for development and presentation of e-study materials, their assessment and presentation considering user needs and requirements of research, as well as literature study research, and, also, based on the foundations of visual science. The focus for the development of Guidelines was particularly on the visual function importance in the reading and learning process, as clear and stable text perception primarily is provided by near visual functions. In a structured manner, there are recommendations presented for a user-friendly e-study material design - style, size, spacing, position, colour - which should be applied for easy perception with visual processes, thus helping the learning process and facilitating memorization.As nowadays there is a growing need for teaching methods and learning environment that is user-oriented, guidance specifics may be different for each of the e-study targeting groups that are divided primarily into three groups: children, adults, and seniors because each group has a different needs, requirements, and visual perception, as well as it is necessary to consider other features of the user which may differ from the standard and affect efficiency of recommendations. This work deals with part of the target group – adults (16-38).